1981
DOI: 10.1016/0020-7292(81)90074-6
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal fibrosis: A two decade experience and gynecologic manifestations

Abstract: A 20-year experience with idiopathic retroperitoneal fibrosis (RPF) is presented (6 cases). Its gynecologic manifestations with the simulation of pelvic malignancy is discussed. Three of the patients presented with pelvic masses, one of these a para-vaginal mass. In one patient, RPF followed or was concurrent with invasive squamous cell carcinoma of the cervix, of which this is the first reported case. The subject of RPF is reviewed with the modes of management and evidence for an autoimmune etiology. Thromboc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Quinidine was promoted by Thomas Lewis for the termination and prevention of atrial fibrillation, 1 after Karel Wenckebach had shown in 1914 that the related drug quinine could halt paroxysms of this arrhythmia. 2 In 1951 Maurice Sokolow reported conversion to normal rhythm with no important side-effects in 80% of 111 personal cases of atrial fibrillation and flutter, using blood level control.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Quinidine was promoted by Thomas Lewis for the termination and prevention of atrial fibrillation, 1 after Karel Wenckebach had shown in 1914 that the related drug quinine could halt paroxysms of this arrhythmia. 2 In 1951 Maurice Sokolow reported conversion to normal rhythm with no important side-effects in 80% of 111 personal cases of atrial fibrillation and flutter, using blood level control.…”
Section: Commentmentioning
confidence: 99%
“…the priorities are to restore adequate ventilation and obtain a pathological diagnosis. 1 The choice of bronchoscopic techniques includes Nd-YAG laser, diathermy and cryotherapy, 2 all of which carry a risk of bleeding. Thereafter, complete resection with primary reconstruction of the airways offers the best chance of cure.…”
mentioning
confidence: 99%
“…2 In 1951 Maurice Sokolow reported conversion to normal rhythm with no important side-effects in 80% of 111 personal cases of atrial fibrillation and flutter, using blood level control.…”
Section: Commentmentioning
confidence: 99%
“…1 The choice of bronchoscopic techniques includes Nd-YAG laser, diathermy and cryotherapy, 2 all of which carry a risk of bleeding. Thereafter, complete resection with primary reconstruction of the airways offers the best chance of cure.…”
mentioning
confidence: 99%